Novel technological possibilities for growth of GaAs autoepitaxial films, and properties of Gunn diodes made on their basis - Belyaev, A.E.; Bobyl, A.V.; Boltovets, N.S.; Ivanov, V.N.; Konakova, R.V.; Konnikov, S.G.; Kudryk, Ya.Ya.; Markovskiy, E.P.; Milenin, V.V.; Rudenko, E.M.; Tereschenko, G.F.; Ulin, V.P.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The n⁺-n-n⁺-n⁺⁺-GaAs epitaxial structures were MBE-grown on porous nanostructured and traditional (standard) heavily doped n⁺⁺-GaAs substrates. On their basis, we fabricated the Gunn diodes generating power output in the 44−59 GHz (first harmonic) and 101−104 GHz (second harmonic) frequency ranges. For both harmonics, the power output of the Gunn diodes grown on porous substrates was shown to be from 20 to 30 % higher than those grown on the flat ones.